Pemberdayaan masyarakat melalui penerapan teknologi pengawetan dan pengolahan batang sawit untuk bahan baku mebel dekoratif - Fakhri Fakhri; Alfian Malik; Pedia Aldy; Elianora Elianora; Zulkifli Zulkifli (Unri Conference Series: Community Engagement, 2020)
Oil palm trunk is one of the biomass that has not been utilized and becomes waste in the former oil palm replanting location. The application of palm oil processing technology for furniture raw materials can provide solutions to target audiences to be utilized and developed in the future. The aim of the community service activity is to assist the processing of oil palm stems for the production of furniture that has distinctive features and high selling value. The method of implementing the activity is theoretical assistance and direct practice to target audiences regarding palm oil processing technology for decorative furniture products. Achievement measurement tools consist of theoretical understanding and application suitability in the field. The results of these activities can be implemented by various prototypes of furniture products. The partner's knowledge of the wood processing business makes the transfer of science and technology for the use of oil palm trunks easier to implement. Socio-economically for the local community is very beneficial because it can change the perception of the existence of palm oil stems which have been considered as waste into a potential that can be utilized for an economically valuable product.